A Tale of Two Tributes: Bowie Remembered at the Grammys and the Brit Awards. Issue 3 (4th May 2018) - Nelligan, Kat; Giuffre, Liz
Abstract : This article explores the politics of remembrance through performance tributes and covers of Bowie's work, specifically the Lady Gaga tribute at The Grammys and Lorde tribute at The BRIT Awards. We consider the specifics of performing cover versions for televised broadcast and post-broadcast, and examine appraisals of both tributes from interdisciplinary perspectives, including popular music, media and gender studies. Each female performer's tribute and their subsequent reception is examined in terms of how discourses of genre, authenticity, gender and queerness are played out through media commentary. We argue that these appraisals are shaped by notions of authenticity and gender stereotypes, and we explore the decisive role the media plays in shaping public taste and preference. Moreover, we argue that the language used to appraise these tributes reveals expectations around what a cover or a tribute should be, and how it should relate to the artist being remembered. Finally, in analysing the performances by Lady Gaga and Lorde queerly, we acknowledge the extent to which Bowie's own queer aesthetic has influenced the music and performance personae of both Lady Gaga and, perhaps to a lesser extent, Lorde.